Data migration, a practical example from the business world - Rintamäki, Lina (My University, 2010)
A high amount of data is being managed by databases and applications in companies today. In many cases data is extracted from several different databases, then managed and finally stored in yet another database. The process of moving data from one database to another is called data migration. The data migration process can eventuate in several new problems, especially considering the high amounts of data that is being processed. In some cases the data migrations are conducted manually, which can be very time consuming. On the software market today there exists several different 'off the shelf' products that manages the data migration process. The problem is to find the one that is most suitable for the company, or to realize that there is none that is suitable enough. The practical work performed behind this masters thesis is the development of an application for data migration that is custom-made for the company Dipcon and their specific needs. In addition to the data migration the application also performs the transformation of the data that is needed before the migration. The more theoretical part of this thesis is focused on the theories and practices behind data migration. Data migration projects are very common, a clear majority of the companies asked in Bloor Reasearch's Data migration in the global are performing a data migration each every 3d month or more often. Even though they are so common, the data migration projects seem to be misunderstood with a more than 60% failure rate. This thesis is discussing the reasons behind this and have some suggestions to add in order to increase the likelihood of a successful data migration.
Keywords: Programvaruteknik; Software Engineering